The frozen river : a novel - Lawhon, Ariel (Doubleday, 2023)
"A gripping historical mystery based on the real-life diary entries of Martha Ballard, an 18th-century midwife who defied the legal system and wrote herself into American history. Maine, 1789: When the Kennebec River freezes, entombing a man in the ice, Martha Ballard is summoned to examine the body and determine cause of death. As a midwife and healer, she is privy to much of what goes on behind closed doors in Hallowell. Her diary is a record of every birth and death, crime and debacle that unfolds in the close-knit community. Months earlier, Martha documented the details of an alleged rape committed by two of the town's most respected gentlemen--one of whom has now been found dead in the ice. But when a local physician undermines her conclusion, declaring the death to be an accident, Martha is forced to investigate the shocking murder on her own. Over the course of one winter, as the trial nears, and whispers and prejudices mount, Martha doggedly pursues the truth. Her diary soon lands at the center of the scandal, implicating those she loves, and compelling Martha to decide where her own loyalties lie"--